ANALISIS PENGARUH PEMELIHARAAN DAN OPERASIONAL TERHADAP KERJA GARBARATA DI TERMINAL 2F BANDAR UDARA INTERNASIONAL SOEKARNO HATTA - Asep Irawan; Nurhedhi Desryanto; Imam Haryadi Wibowo (Politeknik Penerbangan Indonesia Curug, 2018)
Passenger comfort is important for Soekarno Hatta International Airport managers. Work from equipment is needed to maintain airport operations, as well as garbarata. Maintenance and operations are one factor in influencing the work of garbarata. Currently there is still a maintenance facility for damage to garbarata. Therefore, this is examined as a material that determines what is done to better maintain the work of garbarata